Design Of Linear Generator - Ahmad Fuad bin Jamaluddin, Ahmad Fuad (Universiti Teknologi Petronas, 2010)
The objective of this project is to design and develop a prototype of linear motor that could be used to convert mechanical energy into electrical energy and back. In this project. the desired deliverables is a hardware development of linear generator/motor that will produce sufficient electrical energy from a sustained mechanical motion. The challenge of this project is to design a moving iron linear generator that can induce sufficient magnetic flux to produce significant electrical energy.